Optimasi Literasi Digital : Pendampingan Dan Aplikasi Teknologi Untuk Guru Sekolah Dasar Di SD Negeri 033922 Paropo - Sitinjak, Erni Kusrini; Gusar, Martua Reynhat Sitanggang; Marbun, Juliaster (Universitas Pahlawan Tuanku Tambusai, 2024)
This Community Service Program aims to improve the quality of learning at target partner schools, namely UPT SD Negeri 033922 Paropo and UPT SD Negeri 030344 Paropo through learning technology adaptation training activities for teachers. This training needs to be carried out because of the digital literacy gap that occurs among elementary school teachers. In the current digital era, elementary school teachers are required to improve their ability to master information technology. The existence of digital literacy can be a motivation for teachers to be technologically literate and an effort to improve students and learning. Teachers as the front guard play an important role in the implementation of learning and can influence the results of achieving learning objectives. Teachers who have good digital literacy can manage learning more effectively. For this reason, this community service program provides training in the use of learning technology applications for elementary school teachers. Activities include training and practice. The material discussed is compiling teaching materials using the Genially application, compiling questions or quizzes and educational games. The results of this community service activity show that there has been an increase in knowledge and an increase in the ability of elementary school teachers to use learning applications. Overall, this community service activity received a positive response from teachers at SD Negeri 033922 Paropo and SD Negeri 030344 Paropo